Direct measurement of absolute radiation pressure of leds in nanopascal range under ambient conditions with microcantilever - Yuki Takei; Hiromitsu Furukawa (Scientific Reports)
Abstract Optical radiation pressure caused by the force exerted by photons upon interacting with matter represents a crucial phenomenon for exploring physical and biological processes, particularly in the context of optical tweezers. However, accurately measuring the absolute value of radiation pressure presents a significant challenge owing to its inherently small magnitude. Conventional measurement setups are often complex and costly. This study demonstrates the measurement of radiation pressure using a near-infrared light-emitting diode (LED) in ambient conditions, employing a simple and cost-effective experimental setup. The radiation pressure was quantified by measuring the deflection of a highly sensitive microcantilever, achieving pressure measurements as low as 228 nPa, equivalent to a force of 21.5 fN. This represents the smallest absolute value of radiation pressure measured to date and marks the first successful application of an LED in such experiments under standard atmospheric conditions. The simplicity and affordability of this method make it a promising candidate for integration into compact devices for industrial applications, such as full-scale testing of sensitive pressure sensors used in atomic force microscopy, photoacoustic spectroscopy, and advancing the understanding of physical and biological phenomena.